2021
DOI: 10.1016/j.ejrad.2021.109772
|View full text |Cite
|
Sign up to set email alerts
|

Use of CT radiomics to differentiate minimally invasive adenocarcinomas and invasive adenocarcinomas presenting as pure ground-glass nodules larger than 10 mm

Abstract: This study aimed to develop a model based on radiomics features extracted from computed tomography (CT) images to effectively differentiate between minimally invasive adenocarcinomas (MIAs) and invasive adenocarcinomas (IAs) manifesting as pure ground-glass nodules (pGGNs) larger than 10 mm. Method: This retrospective study included patients who underwent surgical resection for persistent pGGN between November 2012 and June 2018 and diagnosed with MIAs or IAs. The patients were randomly assigned to the trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
(35 reference statements)
0
10
1
Order By: Relevance
“…Previous studies have reported that the size of GGNs is a critical risk factor for potential invasiveness (3)(4)(5)21). Lee et al found that the optimal cutoff size for preinvasive lesions was less than 10 mm (sensitivity, 53.33%; specificity, 100%) in a pure GGN cohort; this could be used as a selection criterion to identify patients suitable for sublobar resection (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that the size of GGNs is a critical risk factor for potential invasiveness (3)(4)(5)21). Lee et al found that the optimal cutoff size for preinvasive lesions was less than 10 mm (sensitivity, 53.33%; specificity, 100%) in a pure GGN cohort; this could be used as a selection criterion to identify patients suitable for sublobar resection (25).…”
Section: Discussionmentioning
confidence: 99%
“…Most previous CT-based quantitative studies have used single screening images to estimate the invasiveness of GGNs on the basis of size, density, and mass volume (4,5). However, there are known limitations to this approach owing to inter-and intraobserver variability in morphological features of GGNs.…”
Section: Introductionmentioning
confidence: 99%
“…When the value of l was 0.0118, and log(l) = −1.9293, an optimal subset with 24 non-zero features was yielded. Radiomics converts traditional medical images, applying advanced computational methodologies, into exploitable data information that cannot be captured by the naked eye and carries out high-throughput quantitative analysis on them (26)(27)(28)(29)(30)(31). To our knowledge, this is the first study to classify PC and LAC manifesting a solitary pulmonary solid nodule based on advanced radiomics technology.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is necessary to point out that all SR sections are independent from each other, so that the Patient Clinical Data and Clinical Evaluation sections are optional and may be filled in or not upon user choice, although they were conceived with the aim of creating databases. In fact, the possibility of collecting all these data could allow the creation of a large database, not only for epidemiological studies, but also in the highest conception of radiology, to lay the foundations for radiomics studies [34][35][36][37]. Radiology reports should be rich in data that could potentially be pooled, analyzed and correlated with patient outcomes, thereby assisting future clinical and imaging guidelines.…”
Section: Discussionmentioning
confidence: 99%